Quaternary Sea-Level Changes : A Global Perspective - Murray-Wallace, Colin V.; Woodroffe, Colin D. (Cambridge : Cambridge University Press, 2014)
There have been significant changes in sea level over the past two million years, and a complete understanding of natural cycles of change as well as anthropogenic effects is imperative for future global development. This book reviews the history of research into these sea-level changes and summarises the methods and analytical approaches used to interpret evidence for sea-level changes. It provides an overview of changing climates during the Quaternary, examines processes responsible for global variability of sea-level records, and presents detailed reviews of sea-level changes for the Pleistocene and Holocene. The book concludes by discussing current trends in sea levels and likely future sea-level changes. This is an important and authoritative resource for academic researchers and graduate and advanced undergraduate students working in tectonics, stratigraphy, geomorphology, physical geography, environmental science and other aspects of Quaternary studies.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Pleistocene-Holocene boundary